Bangladesh - Energy Policy Note for the New Government - World Bank (Washington, DC, 2013)
Bangladesh suffers from significant shortages of power generation capacity and natural gas. Addressing these problems will require concerted action to improve services, restructure energy sector finances, and bolster governance. In parallel, fuels and power policymaking coordination should be improved in order to address medium and longer term issues (such as assessing the place of coal-fired power in the generation mix, and considering energy trade options). The World Bank Group is ready to support Bangladesh to address comprehensively its energy sector challenges, complementing the assistance from other development partners.